THE ESSENCE OF UNIVERSAL HUMAN VALUES AND THEIR INFLUENCE ON CHANGES IN THE SPIRITUAL LIFE OF YOUTH - Kurbanov Ilkhomjon Ruzmatovich; Kandov Bahodir Mirzayevich (Zeta Repository, 2023)
In this article, the forms of manifestation of universal human values are of a relative nature, but this relativity is not always noticeable, the forms of manifestation of universal human values are studied. Problems related to universal human values are becoming one of the main topics that attract the attention of philosophers and researchers. The author scientifically analyzed the meaning, structure, main forms, manifestation features and the universal system of values, the place and significance of the main forms of values in this system, since this expression is now widely used.